Jordan : Country Financial Accountability Assessment - World Bank (Washington, DC, 2013)
This Country Financial Accountability Assessment (CFAA) for Jordan is a diagnosis of the country's public and private financial accountability framework, financial management systems and practices. The main objective is to: a) assess whether the existing accountability, as designed and practiced, is sufficient to ensure effective and efficient use of public funds; and b) support the country in the design and implementation of financial management capacity building programs in order to promote transparency and strengthen investor confidence in the management of public and private funds. This CFAA is being undertaken as part of the government program for public sector reform. It is based on discussions with Jordanians government officials, private sector representatives and the desk review of related studies and papers undertaken by the government and the Bank regarding: public sector management; private sector accounting and auditing; and education and training in financial management, and accounting. A key element of the CFAA's recommendation targets the auditing profession, which is called upon to ensure that the profession contribute effectively to enhancing private and foreign investment environment through the promotion of sound, internationally accepted disclosure practices.